2021
DOI: 10.1039/d0na00685h
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scale imaging of dual stable isotope labeled oxaliplatin in human colon cancer cells reveals the nucleolus as a putative node for therapeutic effect

Abstract: Oxaliplatin shows a superior clinical activity in colorectal cancer compared to cisplatin. Nevertheless, the knowledge about its cellular distribution and the mechanisms responsible for the different range of oxaliplatin-responsive tumors...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
3
13
0
Order By: Relevance
“…Since both Pt-alkyne-53 and Pt-azide-64 are clickable with either fluorescent labels or biotin, we propose that they can be used to follow the kinetics of DNA repair, using fluorescent microscopy on cells, or by performing dot blots on genomic DNA. By microscopy, we show that the cisplatin derivatives are distributed within the nucleus, and enriched within nucleoli, an observation which is in line with previous reports ( 21 , 22 ). Platinum compounds are known to also bind RNA and proteins, which are highly abundant in the nucleoli, where transcription of ribosomal RNA occurs ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since both Pt-alkyne-53 and Pt-azide-64 are clickable with either fluorescent labels or biotin, we propose that they can be used to follow the kinetics of DNA repair, using fluorescent microscopy on cells, or by performing dot blots on genomic DNA. By microscopy, we show that the cisplatin derivatives are distributed within the nucleus, and enriched within nucleoli, an observation which is in line with previous reports ( 21 , 22 ). Platinum compounds are known to also bind RNA and proteins, which are highly abundant in the nucleoli, where transcription of ribosomal RNA occurs ( 23 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we hypothesize that the discrete foci we observe in the cytoplasm, especially for Pt-alkyne-53, indicate the formation of aggregates, in agreement with previous observations using isotope-labelled platinum drugs. In this report, it was suggested that the cytoplasmic localization indicated endocytosis of compound aggregates ( 22 ). Moreover, mitochondrial DNA is a known target of cisplatin in addition to nuclear DNA ( 26 , 27 ), therefore co-staining with mitochondrial markers could provide additional information on the nature of these cytoplasmic foci.…”
Section: Discussionmentioning
confidence: 92%
“…5D ). In line with previous observations in adherently grown cell cultures, 40 this could points towards dissociation of the tightly bound DACH ligand from the metal center, which is unexpected, as the DACH ligand is considered as being inert. One explanation for this observation could be that the compound is degraded ( e.g.…”
Section: Resultssupporting
confidence: 87%
“…NanoSIMS has been successfully employed to investigate the cellular fate of the metal center simultaneously to isotopically labeled ligands of different metal-based complexes in cell culture experiments. [38][39][40][41] There are few NanoSIMS studies using this approach to investigate anticancer compounds also in in vivo settings. 33,42 Recently, we succeeded in determining of the subcellular platinum distribution in tumors of KP2156-treated mice.…”
Section: Kp2156 Enters Cancer Cells In Vivo Via the Endo-/lysosomal Pathwaymentioning
confidence: 99%
“…To study the effects of autophagy induction, cells were incubated with DMEM low glucose (fed condition) or Earle's Balanced Salt Solution (EBSS, Sigma-Aldrich, starvation condition) for 2, 4, or 6 h. Since 6 h starvation clearly activated autophagy (Figure 1), further experiments were performed after 6 h incubation with 100 µM CDDP or OX (Teva Pharm, Ulm, Germany) under fed and starvation conditions, as described above, in the presence or absence of 100 nM bafilomycin A1 (InvivoGen Europe, Toulouse, France) as an inhibitor of lysosomal acidification and therefore of autophagy. The concentration of platinum derivatives used in the present work reflects what used in other in vitro studies [60,61]; moreover, in vitro studies show that at this concentration, these substances show a robust interaction with hOCT2 [8,9].…”
Section: Cell Culturementioning
confidence: 59%